ANALISIS KINERJA KELEMBAGAAN TATA NIAGA PASAK BUMI (Eurycoma longifolia Jack) YANG BERKELANJUTAN DI KABUPATEN KUBU RAYA DAN KOTA PONTIANAK, KALIMANTAN BARAT - SM Kartikawati; Ervizal A.M Zuhud; Agus Hikmat; Hariadi Kartodihardjo (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
Pasak bumi (Eurycoma longifolia Jack) is one of the main non forest products actively traded in West Kalimantan. The marketing of pasak bumi presented specific characteristics directly related to the natural environment of pasak bumi. The strong mutual dependency between pasak bumi collectors and traders is central to understanding the marketing of pasak bumi. The main objective of this research is to assess the overall performance of the pasak bumi trading. More specific goals are : (1) to analyze the determining factors of the trading chain, and (2) to analyze the interrelation between marketing characteristics and pasak bumi collectors' and traders' behaviours. The research was carried out in Kubu Raya and Pontianak City,West Kalimantan Province. Primary and secondary data were collected by observation and in-dept interview and analyzed using an institutional analisis development framework. The result showed that institutional pattern of the pasak bumi chain is a typical patron-client system. Low accessibility, asymmetric information, limitation on capital and high value of pasak bumi are all factors directly affecting the marketing institution. Stakeholder that obtained largest margin in trading system and profit margin is trader in the city.